Assessment of in vitro anti-skin ageing activities of Giant Indian Gooseberry (Phyllanthus indofischeri Bennet) extracts for dermatological health and aesthetic applications - Korawinwich Boonpisuttinant; Warintorn Ruksiriwanich; Romchat Chutoprapat; Sarinporn Udompong; Rattiya Kansawang; Jinapa Sangsee; Wirinda Chompoo; Kitrawi Samothai; Ratakorn Srisut (My University, 2023)
Abstract Giant Indian Gooseberry (GIG) are commercially cultivated and commonly used herbs in Traditional medicine especially in Thailand. The aim of this study was to assess the potential of the GIG extracts on anti-aging activities to be a dermatological application. The juice, meat residues, and seeds of GIG collected from Sra Kaeo Province, Thailand, were extracted by the Boiling method (B) and the Maceration process (M) by using 95% ethanol as a solvent. The GIG extracts gave the total phenolic (TPC) and total flavonoid contents (TFC), quercetin contents, as well as exhibited the anti-oxidative activities. The GIG-R-B extract inhibited tyrosinase activity and had the highest anti-melanogenesis activity on B 16 F 10 cells of 31.63 ± 0.70%. The GIG-S-B, GIG-S-M, and GIG-R-M extracts demonstrated the highest collagen biosynthesis, which was comparable to vitamin C ( p < 0.05 ), whereas the GIG-R-B extracts gave the highest stimulation of anti-ageing genes ( SIRT1 and FOXO1 ). All extracts at the concentration of 0.1 mg/mL showed no cytotoxicity on human skin fibroblasts. Therefore, the GIG-S-B extract was discovered to be a promising natural anti-ageing agent for dermatological health and aesthetic applications, that can be further developed in cosmetic, functional food and food supplement industries.
Keywords: Maceration (sewage); Bee Products Chemical Analysis